2016
DOI: 10.1111/cdep.12166
|View full text |Cite
|
Sign up to set email alerts
|

The Privileged Status of Category Representations in Early Development

Abstract: The ability to carve the world into broad categories (e.g., DOG) made up of distinct individuals (e.g., Lassie and Toto) is essential for adaptive behavior and has been the focus of extensive research in cognitive and developmental psychology. Classic work on the development of category representations has revealed that they emerge early: Even infants can conceive of distinct objects as equivalent members of the same category. However, more recently, research on conceptual development has begun to suggest a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 59 publications
0
21
1
2
Order By: Relevance
“…For example, preschoolers readily draw broad, category‐wide inferences after being exposed to only a single member of a novel category (Brandone & Gelman, , ). Preschoolers have also been shown to be highly motivated to acquire information about categories—preferring learning facts and explanations about categories to learning analogous information about individuals (Cimpian, ). Young children also rely on category knowledge over individuating information when making inferences about the future behavior of individual category members (Berndt & Heller, ; Taylor, ).…”
mentioning
confidence: 99%
“…For example, preschoolers readily draw broad, category‐wide inferences after being exposed to only a single member of a novel category (Brandone & Gelman, , ). Preschoolers have also been shown to be highly motivated to acquire information about categories—preferring learning facts and explanations about categories to learning analogous information about individuals (Cimpian, ). Young children also rely on category knowledge over individuating information when making inferences about the future behavior of individual category members (Berndt & Heller, ; Taylor, ).…”
mentioning
confidence: 99%
“…Moreover, they argue that young children are biased to expect information that is intentionally communicated to them to be relevant, important, and generalizable. Indeed, a number of empirical studies have shown that even infants process information differently and form difference expectations when evidence is deliberately manifested for them (Futó et al, 2010;Egyed, Király, & Gergely, 2013;Yoon, Johnson, & Csibra, 2008;) and by early childhood they treat that information as more important and generalizable in a variety of ways (Bonawitz et al, 2011;Butler & Markman, 2012, 2016Butler et al, 2015;Schmidt et al, 2016;Vredenburgh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Seeing novel properties or actions demonstrated intentionally, with cues suggesting the pedagogical intent to transmit important infomation, leads children to make inductive generalizations about that evidence that are stronger and more resistant to counter-evidence (Butler & Markman, 2012b, 2016 Hernik & Cisbra, 2015), leads them to construct radically different conceptions of novel categories (Butler & Markman, 2014;Futó, Téglás, Csibra, & Gergely, 2010;Kovács, Téglás, Gergely, & Csibra, 2016;Yoon, Johnson, & Csibra, 2008), and leads them to infer that Pedagogy and counterevidence 6 the demonstrated action is the only (Bonawitz, Shafto et al, 2011) or normatively correct (Schmidt, Butler, Heinz, & Tomasello, 2016; Vrendenburgh, Kushnir, & Casasola, 2014) way to act. Taken together, this evidence suggests that children's sensitivity to whether or not actions are carried out with pedagogical intent towards the child shapes the inferences children make about the evidence those actions produce.…”
Section: Children's Use Of Social Cues To Guide Inductive Inferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least by age 4, children use this sensitivity to guide their inductive inference process. Pedagogical demonstration of evidence leads children to make inductive generalizations that are stronger and more resistant to counterevidence (Butler & Markman, 2012b, 2016Hernik & Csibra, 2015). It also leads them to construct radically different conceptions of novel categories, for example, organizing their notion of category membership on the basis of deeper, semantic, or functional information rather than shared perceptual features (Butler & Markman, 2014;Fut o et al, 2010;Kov acs, T egl as, Gergely, & Csibra, 2016;Yoon et al, 2008;Yu & Kushnir, 2016).…”
Section: Children's Use Of Social Cues To Guide Inductive Inferencesmentioning
confidence: 99%